Fruit and Leaf Response to Different Source–Sink Ratios in Apple, at the Scale of the Fruit-Bearing Branch - Baïram, Emna; leMorvan, Christian; Delaire, Mickaël; Buck-Sorlin, Gerhard (Frontiers in Plant Science, 2019)
Apple fruit growth is the result of several factors: inherent demand (relative sink strength) of the fruit (defined by the demands for cell division and expansion growth etc.), carbon assimilation by the source leaves (source strength), and the resulting allocation to the organ in question. It is thus a complex process involving source-sink interactions. In the present study, we designed an experimental system in which parts of fruit-bearing branches of two apple cultivars (‘Fuji’ and ‘Ariane’) were isolated from the rest of the tree by girdling and then subjected to specific pruning and fruit removal treatments in order to create a wide range of global (branch-level) source-sink ratios. We monitored fruit kinetics but also photosynthesis as a response to light in leaves of the three different shoot types (i.e. the rosette, the bourse and the vegetative shoots) in order (1) to study the impact of source-sink distance on carbon partitioning between fruits within the same branch and (2) to investigate the impact of source/sink ratio on fruit growth and leaf photosynthetic activity. Our results indicate (1) no significant differences among lateral fruits belonging to different ranks, and this independent of source availability; (2) that a modification of the source/sink ratio seems to be compensated by an alteration of the photosynthetic rate of leaves, with stronger and weaker values obtained for lower and higher ratios, respectively. Moreover, our results seem to suggest that two growing sinks together will upregulate photosynthesis rate more strongly than one growing sink does on its own, and this with the same leaf area per fruit. These results are discussed and some hypotheses are put forward to explain them.